A new genus of Megalonychidae (Xenarthra, Tardigrada) from the Late Miocene of Argentina - Brandoni, Diego (2014)
The present report describes a new genus of Megalonychidae from the Late Miocene of Entre Ríos Province, Argentina, based on a detailed reanalysis of the remains on which "Ortotherium" brevirostrum (Xenarthra, Tardigrada, Megalonychidae) was originally described. "O." brevirostrum differs from O. laticurvatum (type species of the genus) and Ortotherium sp. in: (i) absence of a markedly concavity on the lateral wall of the dentary in "O." brevirostrum, (ii) convexity of the ventral margin of the dentary, (iii) angle between the anterior margin of the coronoid process and the alveolar plane, (iv) length of the diastema, (v) outline of the alveolus of the caniniform, (vi) outline of the molariforms, and (vii) presence of apicobasal grooves extending on the lingual and vestibular surfaces of the molariforms (m1 and m2) in "O." brevirostrum. The presence of these differences suggests that O. laticurvatum and "O." brevirostrum should not be in the same genus. In addition, "O." brevirostrum cannot be accommodated within an existing genus; hence the determination of a new genus of Megalonychidae is justifi ed. The new taxon shows some features (e.g. shape of the alveolus of the caniniform, presence of apicobasal grooves in the molariforms) that are present in some genera of Megalonychidae from the Pleistocene of Central America and Antilles (i.e. Neocnus and Parocnus). This similarity could imply that the genera from the Pleistocene of Central America and Antilles and the new taxon are related.